2021
DOI: 10.1007/s10555-021-09972-4
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint inhibitor therapy for metastatic triple-negative breast cancer

Abstract: Immunotherapy has become a mainstay of cancer treatment in many malignancies, though its application in breast cancer remains limited. Of the breast cancer subtypes, triple-negative breast cancers (TNBCs) are characterized by immune activation and infiltration and more commonly express biomarkers associated with response to immunotherapy. Checkpoint inhibitor therapy has shown promising activity in metastatic TNBC. In 2019, the US FDA granted accelerated approval of atezolizumab, a programmed death-ligand 1 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 77 publications
0
56
0
3
Order By: Relevance
“…In particular, secondary tumors are often more resistant to conventional treatments than primary tumors [1], and local treatments are usually not an option for metastatic patients. In addition, immunotherapy using checkpoint inhibitors only generates a modest response in breast cancer [2]. Despite progress for HER2+ breast cancer [3], polymetastatic breast cancer is still a largely incurable disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, secondary tumors are often more resistant to conventional treatments than primary tumors [1], and local treatments are usually not an option for metastatic patients. In addition, immunotherapy using checkpoint inhibitors only generates a modest response in breast cancer [2]. Despite progress for HER2+ breast cancer [3], polymetastatic breast cancer is still a largely incurable disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…Another phase II study of abemaciclib (selective ATP-competitive inhibitor of CDK4 and CDK6 kinase activity) for TNBC is also ongoing (Clinicaltrials.gov: NCT03130439). CDK inhibitors (mainly CDK4/6) augment anti-tumor immunity through T-cell activation, supporting the rationale for combination with immunotherapy [108,144,145]. A phase Ib clinical breast cancer study of pembrolizumab with abemaciclib demonstrated tolerability with clinical benefits [108].…”
Section: Cyclin-dependent Kinases (Cdks)mentioning
confidence: 95%
“…CDK inhibitors (mainly CDK4/6) augment anti-tumor immunity through T-cell activation, supporting the rationale for combination with immunotherapy [108,144,145]. A phase Ib clinical breast cancer study of pembrolizumab with abemaciclib demonstrated tolerability with clinical benefits [108].…”
Section: Cyclin-dependent Kinases (Cdks)mentioning
confidence: 95%
See 1 more Smart Citation
“…In a phase III clinical trial (KEYNOTE-355), the other ICI, pembrolizumab plus chemotherapy distinctly improved the PFS of patients with metastatic TNBC, compared with placebo plus chemotherapy [ 142 ]. And therefore, Pembrolizumab, was approved in 2020 to treat metastatic TNBC patients with PD-L1-expressing in combination with chemotherapy [ 143 ]. In addition to combining chemotherapy, the combination of ICIs and targeted agents in the treatment of TNBC also has great clinical potential.…”
Section: Immune Checkpoint Inhibitors (Icis)mentioning
confidence: 99%